Passive biaxial mechanical properties of sheep myocardium - Thanyani Pandelani; Letlhogonolo Semakane; Letlhogonolo Semakane; Makhosasana Msibi; Alex G. Kuchumov; Alex G. Kuchumov; Fulufhelo Nemavhola (Frontiers in Bioengineering and Biotechnology)
Introduction: Myocardial infarction is a serious and potentially life-threatening condition that requires immediate medical intervention. The earlier help is provided, the less likely irreversible damage to the heart muscle will occur. Experimental investigation of myocardium behaviour is necessary for advanced numerical models to predict treatment outcomes.Methods: The study investigates the mechanical characteristics of the sheep heart’s mid-wall, right and left ventricles using equi-biaxial mechanical testing. This method allows for studying the myocardium’s behaviour in multiple directions, specifically analyzing the mechanical stiffness and strain energy. Thirteen (13) sheep hearts were collected from a local abattoir, and ten (10) of them were prepared and subjected to equi-biaxial mechanical tests under physiological conditions. This was to ensure that hearts were healthy to minimise the variability in mechanical properties of the myocardium. The study measured stress-strain relationships in both the longitudinal and circumferential directions for the right ventricle (RV), left ventricle (LV), and mid-wall septum (MDW). To minimize viscoelastic effects, the preconditioning protocol involved cyclic loading of 10 cycles before testing.Results and discussion: Results indicated distinct mechanical properties between the chambers, with the RV showing higher strain energy storage and compliance in the circumferential direction than the LV. To minimize viscoelastic effects, the preconditioning protocol involved cyclic loading of 10 cycles before testing. Stress-strain behaviour exhibited nonlinear characteristics, with variability between samples. Stored strain energy values of linear elastic region for left ventricle were 7.317 kJ and 6.67 kJ in longitudinal and circumferential directions, respectively. The elastic modulus was determined from the linear elastic region for each heart wall specifically, from 16% to 40% strain for LV, MDW, and RV. The toe region peak stresses were those corresponding to 16% strain for LV, MDW, and RV. The stresses at 40% strain were obtained from the closest strain level. Anisotropic effects of myocardium were exhibited. Thus, the study provides insights into the mechanical anisotropy of the myocardium and its relevance to ventricular function, offering important data for understanding heart tissue mechanics and modelling heart diseases.